The integration of artificial intelligence technology in english language learning to enhance speaking skills through real-time feedback - Lina Herlina; Mashadi Said (Indonesian Institute for Counseling, Education and Therapy (IICET), 2026)
This research explores the integration of Artificial Intelligence (AI) technology in English language learning to enhance speaking skills through real-time feedback. The study addresses the limited effectiveness of conventional speaking instruction, which often lacks immediate correction and individualized practice. Using a Narrative Literature Review (NLR) approach, data were collected from books, academic journals, and scientific publications related to AI in education, real-time feedback, and speaking skill enhancement. The findings reveal that AI tools such as speech recognition systems and NLP-based chatbots significantly improve learners’ fluency, pronunciation, and confidence by providing instant, adaptive feedback. The study concludes that AI transforms traditional pedagogy into a dynamic, learner-centered model, fostering continuous improvement, engagement, and personalized learning experiences in developing English-speaking proficiency.